Ethnomathematics in the Tumbu Tanah dance: Geometric, rhythmic, and symbolic patterning among the Arfak People of West Papua, Indonesia - Guntur Sada; Jeinne Mumu; Andi Fajeriani Wyrasti; Benidiktus Tanujaya; Falenthino Sampouw; Maryo Sopater Istia (Journal of Honai Math, 2026)
Traditional cultural performances often incorporate sophisticated mathematical concepts through spatial organisation, rhythmic coordination and symbolic systems. However, indigenous performance traditions from eastern Indonesia, particularly West Papua, are underrepresented in the international ethnomathematics literature. This study examines the ethnomathematical structures embedded in the Tumbu Tanah dance of the Arfak people, investigating how mathematical reasoning is enacted through embodied cultural practice. Based on D’Ambrosio’s ethnomathematics framework and Indigenous epistemologies, this qualitative ethnographic study employed participant observation and semi-structured interviews with twelve cultural elders and master performers, alongside systematic visual-kinematic documentation. The data were analysed using a triangulated thematic, geometric and movement analysis approach to identify the mathematical concepts manifested in the dance's choreography, rhythm and social organisation. The findings reveal the Tumbu Tanah dance to be a complex, embodied mathematical system. Three core formations — jey/srem (linear), ikrop (semi-circular) and nimot (circular) — encode geometric principles, including symmetry, rotational transformation, curvature and proportional spatial organisation. Rhythmic foot-stamping patterns exhibit periodicity, recursive sequencing, and collective temporal synchronisation, while the arrangement of dancers by kinship and ceremonial roles reflects indigenous practices of set partitioning, grouping, and numerical distribution. Rather than being transmitted through formal notation, these mathematical ideas are passed on through embodied movement, communal participation, and intergenerational knowledge transfer. By positioning Indigenous dance as a dynamic repository of mathematical knowledge, this study advances the scholarship of ethnomathematics, validates embodied and decolonial epistemologies, and offers actionable pathways for culturally responsive pedagogy, curriculum design and digital heritage preservation.